The Effectiveness of Providing Rewards and Punishment for Moral Development of Early Childhood - Amalia, Dina; Afrianingsih, Anita; Safira Damayanti, Sehla (Universitas Nahdlatul Ulama Surabaya, 2023)
The events that are currently occurring are indeed a lot of problems related to the provision of rewardsand punishment, especially in the parenting patterns given by parents to their children. So it can increaseor even reduce children’s moral development. Therefore, there are many cases of beatings and variouspunishments received by children, such as locking children in their rooms, hitting their body parts, andusing harsh words. This research is a form of social research which aims to analyze and summarizevarious conditions, as a social reality phenomenon in the form of rewards and punishments in the moraldevelopment of early childhood. It involved 39 children from KB Permata Kita Hadiwarno MejoboKudus. Data collection takes the form of observation, interviews, and documentation. The results ofthis research are that through rewards children are more confident and brave in making decisions, whilepunishment can be done through behavioral actions, education and strengthening motivation to avoidunwanted behavior. The conclusion of this research is that through reward and punishment, childrenknow what behavior is right and wrong, so that it has an impact on the child’s character effectively andefficiently to be applied in everyday life.